2010
DOI: 10.1007/s13139-009-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Nucleophilic [18F]-radiolabeling Method with No-carrier-added [18F]fluoride

Abstract: Noninvasive imaging in living subjects with positron emission tomography (PET) provides early detection of diseases in humans. For this application, it is necessary to prepare specific molecular imaging probes labeled with positron-emitting radioisotopes such as fluorine-18 for obtaining high-quality PET imaging. In this review, we describe recent trends in the F-18 radiolabeling method for the introduction of no-carrier-added fluorine-18, which was obtained from an 18 O(p,n) 18 F reaction, into a specific mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Since then, multiple research groups have reported the radiosynthesis of [ 18 F]FLT using this DMTr-Boc-nosyl FLT precursor based on the conventional no-carrier-added radiofluorination method with radiochemical yields ranging from 23-50% (19, 21-24). Particularly, the use of a bulky alcohol as co-solvent in assisting the no-carrier-added radiofluorination is attractive and has been reported to attain [ 18 F]FLT in a high radiochemical yield (60-65%) (25-28). We adapted this high yielding, high selectivity protic solvent chemistry to the EWOD microdevice, and developed a miniature cartridge purification method to eliminate the expensive and complicated HPLC purification.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multiple research groups have reported the radiosynthesis of [ 18 F]FLT using this DMTr-Boc-nosyl FLT precursor based on the conventional no-carrier-added radiofluorination method with radiochemical yields ranging from 23-50% (19, 21-24). Particularly, the use of a bulky alcohol as co-solvent in assisting the no-carrier-added radiofluorination is attractive and has been reported to attain [ 18 F]FLT in a high radiochemical yield (60-65%) (25-28). We adapted this high yielding, high selectivity protic solvent chemistry to the EWOD microdevice, and developed a miniature cartridge purification method to eliminate the expensive and complicated HPLC purification.…”
Section: Discussionmentioning
confidence: 99%
“…Labeling at an aryl or heteroaryl carbon is a favored strategy for this purpose. Consequently, the field of PET radiotracer development has sought to develop a battery of methods for unrestricted introduction of [ 18 F]fluoride ion at aryl and heteroaryl groups in late‐stage radiosynthesis . This review specifically covers the growing utility of hypervalent aryliodine compounds as precursors for use in such methods.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the aminopolyether, Kryptofix 2.2.2 (K 2.2.2; 4,7,13,16,21,24‐hexaoxa‐1,10‐diazabicyclo[8.8.8]hexacosane), as a phase transfer agent for [ 18 F]fluoride ion by the Jülich group greatly facilitated this advance . Although classical S N Ar reactions with [ 18 F]fluoride ion have led to the development of many successful PET radiotracers, and continue to do so, there are limitations in the substrate scope of this method . Generally, homoarene precursors must contain a good leaving group that is activated by an electron‐withdrawing group in the ortho or para position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Despite the short half-life of fluorine-18 (F-18, t 1/2 = 109.8 min), it is the most popular positron-emitter for PET among various radioisotopes owing to its excellent chemical, physiological and nuclear properties. [3][4][5][6][7] The short half-life of F-18, however, requires rapid, simple and reliable F-18 labeling strategies to obtain new PET molecular imaging probes. 8,9 Because angiogenesis associated with the integrin α v β 3 receptor is a key process in tumor growth and metastasis, PET molecular imaging probes for tumor angiogenesis have potential for early tumor diagnosis and monitoring of the therapeutic effects of various treatments in both pre-clinical and clinical studies.…”
mentioning
confidence: 99%